2022
DOI: 10.1097/wnf.0000000000000529
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Valproic Acid Against Coronavirus Disease 2019 Infection or Severity: A Pilot Study

Abstract: ObjectivesThe purpose of the current study was to investigate whether taking valproic acid (VPA) was protective against coronavirus disease 2019 (COVID-19) infection or severity in patients with epilepsy.MethodsThis was a questionnaire study of 150 people who were taking VPA in monotherapy or polytherapy (since the start of the pandemic or longer) and also 150 people who were not taking VPA (since the start of the pandemic), registered in our epilepsy database. The data compared rates of the seropositivity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Although excessive immune responses may also be involved in the pathophysiology of schizophrenia [ 27 , 28 ], it is not known exactly how the immunosuppressive function of VPA affects schizophrenic patients during COVID-19 infection. On the other hand, a pilot study involving 241 epilepsy patients aimed at determining whether VPA had a preventive effect against COVID-19 infection or severe disease did not support the hypothesis of a preventive effect [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although excessive immune responses may also be involved in the pathophysiology of schizophrenia [ 27 , 28 ], it is not known exactly how the immunosuppressive function of VPA affects schizophrenic patients during COVID-19 infection. On the other hand, a pilot study involving 241 epilepsy patients aimed at determining whether VPA had a preventive effect against COVID-19 infection or severe disease did not support the hypothesis of a preventive effect [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…As VPA has been shown to be beneficial in acute respiratory distress syndrome (ARDS), it is thought that the same effect could be achieved in COVID -19 patients, as these patients have excessive release of proinflammatory cytokines in the respiratory system (40). Studies later observed that VPA have positive roles in COVID-19 infection (41,42,43).…”
Section: Vpa and Respiratory Systemmentioning
confidence: 99%